Early Rates of Revision of Knee Cartilage Restoration Surgery and Conversion to Arthroplasty within Five Years. Issue 7 (21st July 2017) - Athiviraham, Aravind; Boyajian, Haroutioun; Lindsay-Rivera, Kevin; Shi, Lewis; Khazai, Ravand
Objectives: To examine the early rates of revision surgery for common knee cartilage restoration procedures performed in the United States, and subsequent conversion to total or unicondylar knee arthroplasty within five years. Methods: Using the MarketScan Research Databases (Truven Health Analytics), we examined all patients who underwent knee microfracture (CPT 29879), autologous chondrocyte implantation (ACI) (CPT 27412) or osteochondral grafting (CPT 27415, 27416, 29866, 29867), within the encompassed timeframe (2003-2014), and who remained tracked within the system for two contiguous years post-operatively to assess rate of revision surgery for complications and five contiguous years to assess revision to either total or unicondylar knee arthroplasty. Results: Although microfracture remains the most common articular cartilage restorative procedure, its rates have been slowly declining since 2009, where as rates of ACI and osteochondral grafting have remained relatively stable (Image). 76, 304 microfracture patients, average age 48.3 (SD=13.6), with minimum follow-up of 2 years were examined. 6, 366 patients (8.3%) underwent at least one revision cartilage procedure within two years. 93% of these patients had either repeat microfracture or chondroplasty, 4.7% underwent osteochondral grafting, and 2.3% underwent ACI. 1, 030 patients (1.3%) required repeat surgery secondary to stiffness or infection: 94% of these patients required manipulation under anesthesia (MUA) and the remaining 6% required open or arthroscopic incision and drainage (I&D). 24, 892 patients who underwent microfracture were enrolled for at least 5 years. 428 (1.7%) of these patients subsequently underwent knee arthroplasty within 5 years. Of the 868 patients who underwent ACI as the index procedure, 139 patients (16.0%) underwent a revision cartilage procedure within two years; most commonly chondroplasty (77.8%). Average age of ACI patients was 34.5 (SD=13.5). 46 ACI patients (2.1%) returned to the OR for complications; most commonly MUA for stiffness (98.3%). Of the 233 ACI patients who were enrolled for 5 years, 16 (6.9%) of patients underwent knee arthroplasty. 2, 151 patients underwent osteochondral grafting as the index procedure, with the average age being 34.5 (SD=14.1). 331 (15.4%) patients underwent revision cartilage surgery, most commonly arthroscopic chondroplasty (52.6%). 107 (5%) of patients underwent surgery for complications, most commonly MUA (80.3%). Of the 741 patients who underwent osteochondral grafting that were enrolled for 5 years, 16 (2.2%) subsequently underwent conversion to knee arthroplasty. Conclusion: While the incidence of arthroscopic microfracture has been slowly decreasing since 2009, it remains the most common cartilage restorative procedure performed in the USA. Of the procedures examined, those undergoing ACI were more likely to require subsequent chondroplasty, where as patients undergoing osteochondral grafting were more likely to require MUA for stiffness. Conversion to arthroplasty within five years was lowest in the microfracture group and highest in the ACI group. The most common revision cartilage procedure was chondroplasty and most common complication requiring surgery was stiffness in all groups. Data from this study may help providers better inform patients on the rates of revision surgery and efficacy of these procedures in delaying total joint arthroplasty.